Evaluate orthotropic properties of wood using digital image correlation. (15th June 2016) - Jeong, Gi Young; Park, Moon Jae
Highlights: Elastic properties and ratios from four different wood materials were determined. Poisson's ratio from four different wood materials was determined. Strength and failure behavior from four different wood materials were determined. Off-axis tension test with DIC was used to evaluate the orthotropic properties. Abstract: The goal of this study is to evaluate the orthotropic properties of four different wood species. Off-axis tension tests with digital image correlation were used to evaluate the orthotropic properties of Larix kaempferi, Pinus densiflora, Pinus koraiensis, and Cryptomeria japonica . The highest elastic modulus EL of 11.70 GPa was found from Larix kaempferi, whereas the lowest elastic modulus ER of 0.12 GPa was observed from Cryptomeria japonica . The highest shear modulus GLT of 2.68 GPa was found from Larix kaempferi and the lowest shear modulus GLR of 0.32 GPa was observed from Cryptomeria japonica . While the shear modulus values in the LT plane from the four species were higher, the shear strength values in the LR plane were higher than those in the LR plane. Poisson's ratios from the four species were found that νRT and νTR were higher than νLR and νLT . Although mixed failure behaviors were found from the four species, the failure behaviors were dominantly influenced by the orientation of the specimens.